Gangguan Fungsi Kognitif Berkontribusi Terhadap Penurunan Kualitas Hidup Penyintas Kanker Payudara Pasca-kemoterapi - Syarif, Hilman; Waluyo, Agung; Afiyanti, Yati; Mansyur, Muchtaruddin (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Decreased cognitive function sometimes dramatically affects the function, quality of life and integration ofcancer survivors in the community. The objective of this study was to identify the relationship of cognitivefunction to the quality of life of post-chemotherapy breast cancer survivors. This comparative descriptivestudy uses a cross-sectional design at Dharmais Cancer Hospital, Jakarta. A total of 110 samples weredetermined by purposive sampling method. The questionnaire used to identify cognitive function is theIndonesian version of the Montreal Cognitive Assessment (MoCA), known as the MoCA-Ina. Thequestionnaire used to measure quality of life is EORTC QLQ C30. A total of 69 (62.7%) respondentsexperienced a decline in cognitive function. Based on cognitive function scores, the average visuospatial /executive is 4.30 (0.80), naming 2.76 (0.45), attention 4.25 (1.16), language 2.39 (0.80), abstraction 1.63(0.52), delayed recall 2.17 (1.01), and orientation 5.88 (036). The mean global health status score was lowerin the group with decreased cognitive function compared to the normal group, which was 56.76 (13.04) and79.47 (10.05), p <0.001. Decreased cognitive function contributes to quality of life. Assessment of cognitivefunction is recommended as a routine assessment by nurses and interventions to improve the quality of lifeof survivors.